2019
DOI: 10.1007/s11356-019-04353-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of the proangiogenic properties of chlordecone and three of its dechlorinated derivatives formed by in situ chemical reduction

Abstract: The results presented here were obtained through financing by the French Ministry of Environment, General directorate for risk prevention (action F of the 2015 grant program MEDDE/BRGM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Crude incidence, cases/100,000 male inhabitants Crude mortality, deaths/100,000 male inhabitants Ratio mortality to incidence, % environmental pollutants linked to the PCa development [41]. Another environmental pollutant is the widely discussed Bisphenol A (BPA) also studied in context of PCa.…”
Section: Countrymentioning
confidence: 99%
“…Crude incidence, cases/100,000 male inhabitants Crude mortality, deaths/100,000 male inhabitants Ratio mortality to incidence, % environmental pollutants linked to the PCa development [41]. Another environmental pollutant is the widely discussed Bisphenol A (BPA) also studied in context of PCa.…”
Section: Countrymentioning
confidence: 99%
“…No in vitro tests have shown any greater toxicity in the degradates compared to the parent compound, and several tests have even shown that toxicity decreases as CLD dechlorination proceeds (Legeay et al, 2018). An in vivo test, which matched the human model most closely (Alibrahim et al, 2019), showed a significant decrease in toxicity for CLD-3Cl and CLD-4 Cl compared to CLD.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of complete mineralization, there is always a risk that the byproducts may retain a similar toxicity or acquire a higher toxicity than the parent molecule (Benoit et al 2017;Dol ng et al 2012). To answer this question, the genotoxic, mutagenic and proangiogenic properties of 3 major CLD derivatives, formed during the ISCR process (i.e., isomers having lost 1, 3 and 4 chlorine atoms), were compared to those of CLD (Alibrahim et al 2020;Legeay et al 2017). These studies showed that, like CLD, these derivatives were non-genotoxic and non-mutagenic, while their proangiogenic properties tested both in vitro and in vivo were strongly reduced.…”
Section: Introductionmentioning
confidence: 99%